EFFECT OF HERBICIDE AND INSECTICIDE COMBINATION AGAINST WEEDS ( AINST WEEDS (CONVOLVULUS ARVENSIS AND CELOSIA ARGENTEA) AND SUCKING PESTS IN SOYBEAN - RAJENDRA LAKPALE, DUJESHWER KURREY,; R. P. N.2, SAXENA,; SAHU, PREM LAL (The Bioscan, 2016)
A field experiment was conducted at Research Farm of IGKV, Raipur during Kharif 2013 and 2014 to evaluate the combined effect of herbicide and insecticide against the weed (Convolvulus arvensis and Celosia argentea),sucking pest (including jassid, aphid and white fly) and yield in soybean. All the herbicidal treatments recorded significantly at par in reducing weed count and weed dry matter. Imazathapyr 10 SL@1.0 l ha-1 recorded lowest weed count, weed dry matter and highest weed control efficiency (94.81% and 99.59% in 2013 and 2014 respectively). Rynaxypyre 20 EC @100 ml ha-1 recorded lowest pest count (1.18 insect plant-1) in 2013 but in 2014, Indoxacarb 14.5 EC @ 300 ml ha-1+ Imazathapyr 10 SL @1.0 l ha-1 recorded lowest pest incidence (2.12 insect plant-1). The highest seed yield (2323 kg ha-1), net income (63655 ¹ /ha) and B:C ratio (3.09) was recorded under Imazathapyr 10 SL@1.0 l ha-1 in 2013. Whereas, in 2014, the highest seed yield (2459 kg ha-1) was recorded by indoxacarb 14.5 EC @ 300 ml ha-1+ imazathapyr 10 SL @1.0 l ha-1 and highest net income (67767 ¹ ha-1) was recorded under indoxacarb 14.5 EC @ 300 ml ha-1+ imazathapyr 10 SL @1.0 l ha-1 but B : C ratio (3.27) was superior under quinolphos 25 EC @1.5 l ha-1 + quizalophop ethyl 5 EC @ 1.0 l ha-1.